2010
DOI: 10.1510/icvts.2010.238212
|View full text |Cite
|
Sign up to set email alerts
|

The stented elephant trunk procedure combined total arch replacement for Debakey I aortic dissection: operative result and follow-up

Abstract: The stented elephant trunk technique in aortic arch replacement combined with transaortic stented graft implantation into the descending aorta has been introduced as a means of eliminating the residual false lumen in the descending thoracic aorta and improving long-term outcomes of surgical intervention for Debakey I aortic dissection. This report summarizes the operative and follow-up data with this new procedure. Between August 2004 and May 2009, 28 stented elephant trunk operations were performed for Debake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…According to a German study in 2008, the hybrid operation of total arch replacement with an SET was found to be equivalent to the conventional operation (total arch replacement only) with respect to in-hospital mortality and morbidity. The results of other studies on the use of SET grafts were similar [1,3,4]. The SET procedure has advantages such as false lumen obliteration of the descending aorta.…”
Section: Discussionsupporting
confidence: 62%
“…According to a German study in 2008, the hybrid operation of total arch replacement with an SET was found to be equivalent to the conventional operation (total arch replacement only) with respect to in-hospital mortality and morbidity. The results of other studies on the use of SET grafts were similar [1,3,4]. The SET procedure has advantages such as false lumen obliteration of the descending aorta.…”
Section: Discussionsupporting
confidence: 62%
“…Although the false lumen thrombosis is observed in 80-100% in the stented segment of the proximal descending aorta (18,21,22,25), complete false lumen thrombosis rate after hybrid type A dissection repair is limited to 17-50% (9,12,20,23), which is similar to that of total arch replacement with elephant trunk (43-63%) (3,5). Despite the fact that the history of the hybrid approach in the type A dissection is relatively short, the reported distal reoperation rate is 0-14% (9,12,(18)(19)(20)(22)(23)(24)(25)(26) and has no superiority to total arch replacement with elephant trunk (0-13%) (2,3,5,16). In addition to the distal reinterventions, adjunctive procedures such as branch vessel intervention or additional stenting to cover endoleak or SINE, are often performed after the hybrid approach.…”
Section: Distal Reoperationmentioning
confidence: 94%
“…Cerebral spinal drainage, perfusion of left subclavian artery and distal perfusion with balloon occlusion technique are utilized by some groups to avoid SCI in hybrid approach (22)(23)(24). In fear of SCI, the commonly used length of endograft is around 10-15 cm (9,(19)(20)(21)25), which is shorter than the average length of endografts used in type B dissection. This shorter endograft may be controversial in terms of positive aortic remodeling.…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
See 2 more Smart Citations